(untitled) ("Journal "U". Economy. Management. Finance.", 2023)
The authors consider the topic of interaction between information technology and management in the modern world. The main aspects of the interaction of information technologies in management are also considered and what impact the mutual influence of managers and developing technologies has on the overall structure of the enterprise. The impact of IT on quality management in enterprises. The areas in the work of the enterprise where information technology can be particularly useful in solving any tasks are considered.